A Researcher’s Methodological Approach in a Dissertation of Master of Philosophy in Mathematics Education in Nepal - Bhattarai, Yubaraj (Academic Journal of Mathematics Education, 2022)
This paper explores on methodology approach applied for explaining assessment of mathematics to excavate assessment practices of students and teachers at secondary level in the context of Nepal. The paper uncovers the methodology section of a dissertation entitled "Assessment in Secondary Level Mathematics: A Narrative Inquiry" submitted to Nepal Open University to acquire a degree of masters of Philosophy in Mathematics Education. I portray the related phenomena to my research questions from ontological, epistemological, axiological, and rhetorical considerations. Then I describe methodological considerations related to research paradigm, research design, and sampling of data. Furthermore, I explore the data collection and analysis of my study, dividing it into different subheadings. I have thrown light on quality standards and ethical consideration followed in the research. The paper further excavates the data analysis, data interpretation of the methodology section of the dissertation. Finally, the paper concludes with discussion and conclusions about the applied methodology to conduct the study on mathematics assessment at secondary level in Nepal.